2021
DOI: 10.3390/jof7090704
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Laboratory Mutants of Fusarium oxysporum f. sp. niveum Resistant to Prothioconazole, a Demethylation Inhibitor (DMI) Fungicide

Abstract: Fusarium oxysporum f. sp. niveum (FON) is the causal agent of Fusarium wilt in watermelon, an international growth-limiting pathogen of watermelon cultivation. A single demethylation inhibitor (DMI) fungicide, prothioconazole, is registered to control this pathogen, so the risk of resistance arising in the field is high. To determine and predict the mechanism by which FON could develop resistance to prothioconazole, FON isolates were mutagenized using UV irradiation and subsequent fungicide exposure to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Inoculation was done by adding 5 cork drill bits (diameter 1.0 cm) colonies of each fungal isolate. The inoculated media was then incubated for 7 days using a shaker at 150 rpm at room temperature (Hudson et al, 2021). Next, the Erlenmeyer flask was removed from the shaker and stored for 12 weeks at room temperature to determine the shelf life of each fungal isolate.…”
Section: Propagation Of the Pathogenic Fungi Isolatesmentioning
confidence: 99%
“…Inoculation was done by adding 5 cork drill bits (diameter 1.0 cm) colonies of each fungal isolate. The inoculated media was then incubated for 7 days using a shaker at 150 rpm at room temperature (Hudson et al, 2021). Next, the Erlenmeyer flask was removed from the shaker and stored for 12 weeks at room temperature to determine the shelf life of each fungal isolate.…”
Section: Propagation Of the Pathogenic Fungi Isolatesmentioning
confidence: 99%
“…Setelah medium tersebut dingin, larutan konidium sebanyak 100 mL L -1 ditambahkan (Soesanto et al, 2021). Selanjutnya jeriken ditutup rapat dan diinkubasi dengan cara digoyang secara manual sampai homogen selama 14 hari (Hudson et al, 2021). Setelah diinkubasi, kepadatan konidia dihitung menggunakan haemositometer untuk menentukan tingkat pengenceran, dan diperoleh kepadatan konidia 10 6 konidia mL -1 .…”
Section: Penyiapan Ekstrak Kasar Metabolit Sekunderunclassified
“…However, many studies have reported an increase in the fungicide-resistant strains of several types of pathogens [25]. Notably, the major plant pathogen F. oxysporum, which affects tomatoes, potatoes, dragon fruit, and other commercial crops, has demonstrated resistance to various fungicides, including difenoconazole and tebuconazole [26,27]. Understanding the sensitivity of pathogens to various fungicides and employing appropriate doses are critical for effective chemical control of the disease, as well as environmental protection.…”
Section: Introductionmentioning
confidence: 99%